Health Problems of Scavengers: The Case of Kathmandu Metropolitan City, Nepal - Avasthi, Tara Prasad (The Third Pole: Journal of Geography Education, 2014)
Present paper examines health problems of scavengers. The Study concentrates on the group of people who normally carry out activities such as collection and selling waste paper, dirty plastic, iron, scrap metal and other materials of dumping site. Findings are based on the survey of 40 scavengers of Teku dumping site, Kathmandu. The study indicates that the occupation seems highly risky and most vulnerable for their health. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11513 The Third Pole: Journal of Geography Vol.8-10, pp. 57-61: 2010